The Subjectivity and Futurity of the Asian Canadian Woman - Annie Chau (Atlantis)
This article asserts that subjectivity and futurity are critical sites of contestation between Asian Canadian women and the nation-state of Canada. It draws on primary research involving Asian Canadian women in the spring of 2022: a participant observation of a Canadian citizenship ceremony held virtually during Asian Heritage Month and an interview with Ellen (pseudonym), a member of the Asian Canadian Women’s Alliance. First, in my analysis of the citizenship ceremony, I argue that the figure of the Asian Canadian woman is bound to her allegiance to the nation-state. In the ceremony, discourses of Canadian multiculturalism and the model minority myth are conjoined and pronounced. Second, turning to my interview with Ellen and to instances of resistance by Asian Canadian women during the citizenship ceremony, I argue that Asian Canadian women confront Canadian nation-building and the model minority myth through their articulations and utterances of diversity, feminisms, and decolonization. With Asian Canadian women working to take back their futures from Canada, I propose that possibilities for collective and decolonial futures with Indigenous Peoples can also be imagined.